스켈링 불안 및 공포에 음악중재가 미치는 영향 - 김기욱(Gi-Ug Kim); 이정화(Jung-Hwa Lee); 김지화(Ji-Wha Kim) (한국구강보건과학회지, 2019)
Objectives: The purpose of this study was to classify subjects who participated in a dental hygiene course training in regional A university into an experimental group and a control group. Methods: The anxiety and fear before and after the music intervention and the anxiety and fear before and after the scaling in the experimental and control groups were analyzed by a paired t-test. Results: The scores were 1.824±.866 points before music mediation and 1.110±.288 points after music mediation. The anxiety decreased after music mediation, and there was a statistically significant difference in all subregions and average scores (p<.001). The scores for dental anxiety decreased after the scaling in both groups (p>.05). The experimental group also showed more decreases (t=−2.020, p<.05). Conclusions: In conclusion, music intervention in removing dental plaque was analyzed to affect the reduction of dental fear anxiety, and it is necessary to develop systematic programs and systems that can utilize music in dental treatment. KCI Citation Count: 2